Tacitus’ Germania and the Limits of Fantastic Geography - Lightfoot, Jessica (Histos, 2020)
This article explores Tacitus’ careful, simultaneous positioning of geographical boundaries and the limits of his own writing at the opening and close of the Germania. Three main aspects of Tacitus’ engagement with broader debates concerning the place of mythic and poetic accounts in contemporary geography and ethnography are examined: the treatment of the supposed visits of Hellenic heroes to Germania; the portrayal of Ocean as a significant geographical and metaphorical boundary; and the strict rejection of fantastic ethnography. This examination both elucidates the Germania’s relationship with traditions of geographical and ethnographic writing and points to Tacitus’ portrayal of the region as a potentially conquerable space.